Analisis Modul Ajar Biologi pada Implementasi Kurikulum Merdeka - Sandi Laili Magfiroh; Dika Agustia Indrati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the suitability of the biology teaching module of class X at SMA Negeri 5 Tuban with the standard of teaching module components in the implementation of the Independent Curriculum. This study uses a descriptive method with a qualitative approach. The object of the research is in the form of biology teaching modules for class X odd semesters compiled by biology subject teachers. Data collection was carried out through document analysis and observation, while data analysis was focused on the review of general information components, core components, and attachments to teaching modules. The results of the study show that the teaching module as a whole has been made in accordance with the applicable provisions and is included in the appropriate category. Most of the components of the teaching module have been fulfilled well, although there are still some components that need to be improved, especially in the elaboration of student targets and enrichment and remedial planning. This study shows that the biology teaching module for class X is suitable for use as a learning tool in the Independent Curriculum, but still needs to be refined to be more adaptive to the learning needs of students.